Mobile robot simulator with jmonkeyengine (java base programming) - Ng, Weng Kai (2015)
Simulation has become an important part in design or development for an autonomous robot. Most simulation comes with accurate physic simulation, multi platforms, high quality rendering and open source code. There are several reasons indicated that computer simulation is essentially tool for robotics field, particularly for mobile autonomous robot. Firstly, robots are fragile and hard to test and develop due to their complexity. The ability to test and develop in simulation as in real world environment can reduce the risks and cost of hardware failure. Moreover, there will be costly in develop a robot if the risk of failure is high. Simulations allow us to test the robot in software while waiting for the delivery of components. Nowadays, service robots are becoming more and more visible in daily life. We can see that many countries have been started to undergo research on service robots. Even we search for services robot on YouTube, I can fairly certain that all the results can be summed into one little word, robot. Many researchers have been done on service robot by different organization. There are 2 types or service robot, remote controlled and autonomous. In ecological applications, service robots are used to collect waste and dangerous item in indoor and outdoor environment.